Dimensional effects of nanostructured Mg/MgH2 for hydrogen storage applications: A review. (May 2017) - Sadhasivam, T.; Kim, Hee-Tak; Jung, Seunghun; Roh, Sung-Hee; Park, Jeong-Hun; Jung, Ho-Young
Abstract: Hydrogen is regarded as an ideal fuel for vehicle applications owing to its high chemical energy. However, for on-board energy storage, fuel cell electric vehicles need compact, light, and affordable hydrogen storage system to replace the pressurized hydrogen tanks. In this regard, various materials and composites have been developed for denser and safer hydrogen storage. Among them, Mg is considered as a highly promising material to store the hydrogen in terms of gravimetric and volumetric capacity. However, because of its higher thermodynamic stability and sluggish hydrogen sorption kinetics, the sorption temperature is high and the sorption time is long, limiting for practical usage. Nanoscale material designs with various dimensionalities that have been extensively studied and used in countless research and development sectors, which can provide new strategies to tackle the limitations of Mg based hydrogen storage system. This review describes the fundamental properties, preparation, activation kinetics and thermodynamic stability of various nanostructured Mg/MgH2 materials (including bulk particles, nanofilms, nanowires and nanoparticles confined in nanoporous carbon structures and encapsulated by polymers) for feasible hydrogen storage applications, and summarizes their dimensional effects.